Racial disparities in debt collection - LaVoice, Jessica; Vamossy, Domonkos F. (Journal of Banking & Finance, 2024)
This paper documents that Black and Hispanic borrowers are 52% more likely to experience a debt collection judgment compared to their counterparts, controlling for socioeconomic variables including income, credit scores, delinquent debt balances, and other relevant credit characteristics. Statistical discrimination mechanisms such as spatially targeting collection efforts based on the likelihood that an attorney represents the defendant or that the defendant will contest the debt in court do not explain the racial gap in judgments. We find support that the judgment gap is partially driven by taste-based discrimination, as evidenced by minorities having less 90-day past due debt balances than non-minority borrowers when controlling for model covariates. Furthermore, the disparity primarily affects non-delinquent borrowers, indicating higher levels of creditor discretion in initiating judgment proceedings. A back-of-the-envelope calculation suggests that the racial wealth gap explains at most 48% of the racial disparity in judgments.